Estimates of COVID-19 Impacts on Learning and Earning in Indonesia : How to Turn the Tide - Yarrow, Noah (World Bank, Washington, DC, 2020)
The authors use the World Bank’s recently developed country tool for simulating Coronavirus 2019 (COVID-19) impacts on learning and schooling outcomes and data from the forthcoming Indonesia education service delivery indicator survey to simulate and contextualize the potential impact of COVID-19 school closures on learning outcomes, proficiency levels, enrollments, and expected earnings for Indonesian students in primary and secondary school. The authors estimate that Indonesian children have already lost 11 points on the program for international student assessment (PISA) reading scale and United States (U.S.) 249 dollars in future annual individual earnings due to the four-month closure period from March 24 to the end of July 2020. The authors provide estimates for six- and eight-month closure scenarios, showing that these losses are expected to increase in the coming months as schools gradually re-open (and possibly re-close). To turn the tide of these human capital losses, districts, provinces, and the central ministries should prepare for both improved face-to-face instruction, as well as improved quality of distance education, in order to recapture lost learning and improve overall system quality and resilience to possible future shocks.